2008
DOI: 10.1073/pnas.0810926105
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine in the tuberomammillary nucleus inhibits the histaminergic system via A 1 receptors and promotes non-rapid eye movement sleep

Abstract: Adenosine has been proposed to promote sleep through A1 receptors (A 1R's) and/or A2A receptors in the brain. We previously reported that A 2A receptors mediate the sleep-promoting effect of prostaglandin D2, an endogenous sleep-inducing substance, and that activation of these receptors induces sleep and blockade of them by caffeine results in wakefulness. On the other hand, A 1R has been suggested to increase sleep by inhibition of the cholinergic region of the basal forebrain. However, the role and target si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(82 citation statements)
references
References 37 publications
1
81
0
Order By: Relevance
“…Another group of animals (n = 6) received DMSO or SB 334867 (0.5 μg) (whichever was not applied on the second day) followed by orexin A (10 pmol) application on day 2 or 4 randomly. by SLEEPSIGN software, according to the methods described previously [23][24][25] .…”
Section: Procedures 2: Effect Of Orexin Receptor 1 Antagonist Applicatmentioning
confidence: 99%
“…Another group of animals (n = 6) received DMSO or SB 334867 (0.5 μg) (whichever was not applied on the second day) followed by orexin A (10 pmol) application on day 2 or 4 randomly. by SLEEPSIGN software, according to the methods described previously [23][24][25] .…”
Section: Procedures 2: Effect Of Orexin Receptor 1 Antagonist Applicatmentioning
confidence: 99%
“…Adenosine is a purine nucleoside; it is a by-product of ATP hydrolysis and might represent a cellular signal for energy demand in the brain (Benington and Heller 1995;Chagoya de Sanchez et al 1993). Adenosine has been shown to promote slow-wave sleep and rapid eye movement (REM) sleep in cats and rats (Basheer et al 2004;PorkkaHeiskanen et al 2002;Radulovacki 1995;Radulovacki et al 1984) and more recently in mice (Coleman et al 2006;Oishi et al 2008;Urade et al 2003;Van Dort et al 2009). In the early 1990s it was hypothesized that adenosine accumulates in the extracellular space during waking where, on reaching sufficiently high extracellular levels, it could produce sleep through inhibition of wake-active neurons, in particular those of the basal forebrain (BF) (Rainnie et al 1994).…”
mentioning
confidence: 99%
“…The R,A 1 R antagonist CPT blocked these effects induced by PF (Liu et al, 2005;Zhang et al, 2009). The R,A 1 R agonist increases sleep after perfusion into the basal forebrain and TMN (Murillo-Rodriguez et al, 2004;Oishi et al, 2008). The unilateral infusion of an R,A 1 Rselective antagonist into the basal forebrain decreased sleep (Strecker et al, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…The A 1 Rs are widely expressed in the cortex, thalamus, hippocampus, and basal ganglia regions (Thakkar et al, 2002;Huang et al, 2007Huang et al, , 2011Oishi et al, 2008;Lazarus et al, 2013). Oishi et al (2008) reported that R,A 1 R was highly This work was supported in part by grants-in-aid for scientific research from the National Natural Science Foundation of China (81420108015, 81301135, 31171010, 31171049, 31121061, 31271164, J1210041, 31471064, 31421091,81420108015, 31530035), the National Basic Research Program of China (2015CB856401, 2011CB711000), a key laboratory program of the Education Commission of Shanghai Municipality (ZDSYS14005), the Shanghai Committee of Science and Technology (13ZR1403200, 14JC1400900, 13dz2260700, 13140903100), and the Shanghai Leading Academic Discipline Project (B119).…”
Section: Introductionmentioning
confidence: 99%